Telling truth from Ys: an evaluation of whether the accuracy of self-reported semen exposure assessed by a semen Y-chromosome biomarker predicts pregnancy in a longitudinal cohort study of pregnancy. (13th March 2014) - Rosenbaum, Janet E; Zenilman, Jonathan; Melendez, Johan; Rose, Eve; Wingood, Gina; DiClemente, Ralph
Abstract : Objectives: Adolescents may use condoms inconsistently or incorrectly, or may over-report condom use. This study used a semen exposure biomarker to evaluate the accuracy of female adolescents' reports of condom use and predict subsequent pregnancy. Methods: The sample comprised 715 sexually active African-American female adolescents, ages 15–21 years. At baseline, 6 months and 12 months, participants completed a 40-min interview and were tested for semen Y-chromosome with PCR from a self-administered vaginal swab. We predicted pregnancy from semen exposure under-report using multivariate regression controlling for oral contraception, reported condom use and coital frequency. Results: At the 3 surveys, 30%, 20% and 15% of adolescents who reported always using condoms tested positive for semen exposure. At 6 month follow-up, 20.4% and 16.2% of the adolescents who under-reported semen exposure reported pregnancy, a higher pregnancy rate than accurate reporters of semen exposure, even accurate reporters who reported never using condoms (14.2% and 11.8%). Under-reporters of semen exposure were 3.23 (95% CI (1.61, 6.45)) times as likely to become pregnant at 6-month follow-up and 2.21 (0.94, 5.20) times as likely to become pregnant at 12-month follow-up as accurate reporters who reported not using contraception, adjusting for self-reported coital frequency. Conclusions: Adolescents who under-report semen exposure may be at uniquely high risk for unplanned pregnancy and STIs, and may also under-report coital frequency. Condom efficacy trials that rely on self-report may yield inaccurate results. Adapted to a clinical setting, the Y-chromosome PCR could alert women to incorrect or inconsistent condom use.